Short Communication : Near-isogenic lines in NP 4 background carrying the genes Lr1, Lr2a, Lr2c, Lr3a, Lr9, Lr10, Lr15, Lr17a and Lr20 as locally adapted differentials for Indian pathotypes of wheat leaf rust - Kaushal, Kamini; Bhardwaj, S.C.; Mishra, A.N.; Upadhyaya, Y.M.; Prasad, S.V. Sai; Pandey, H.N. (The Indian Journal of Genetics and Plant Breeding, 2016)
Wheat leaf rust differentials being used in India include selected near-isogenic Lr lines in ‘Thatcher’ background (set A), some of the historical differentials like Malakoff, Webster, Loros etc. (set B) and IWP 94 (Lr23) out of a set of eight Indian wheat genotypes (set 0). The set A lines and most varieties in set B are late maturing as they require long photoperiod for flowering, which limits their utilization in virulence analysis and genetic studies under Indian conditions. A backcross programme was conducted to transfer those Lr genes which occur in these lines and varieties in the background of NP 4 having desired agronomic traits. Nine homozygous resistant lines carrying Lr1, Lr2a, Lr2c, Lr3a, Lr9, Lr10, Lr15, Lr17a, and Lr20 have been developed through six backcrosses and subsequent selection based on seedling tests with appropriate leaf rust pathotypes of selected BC6F3lines having NP 4 plant type. These lines being locally adapted and early maturing are easy to maintain under Indian conditions, and can be widely used for virulence analysis and genetic studies.